Comparison of anxiety scores between unexplained primary and secondary infertile couples - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS LTD, 2021)
Objective To investigate the anxiety levels among infertile women and their partners also factors that may affect the anxiety status Study design A total of 403 infertile couples who applied to Infertility Outpatient Clinics of a University-affiliated Teaching and Research Hospital were included in the study. The infertile group was divided into two groups as primary and secondary infertile. One hundred and thirty-two fertile couples who applied to Gynecology Outpatient Clinics composed the control group. Hamilton Anxiety Rating Scale (HAM-A) form was filled by the infertile couples to evaluate the anxiety status before they started their treatment. Results Three hundred and twenty infertile and 84 fertile couples completed the study. The mean total scores of HAM-A of women were similar between the groups. So were the scores of their husbands. In all groups, women had significantly higher mean total HAM-A scores than their husbands. There was no association between the mean HAM-A score of women and age, BMI, AFC, duration of marriage, duration of infertility, number of previous treatment cycles. Education status, working status and family structure of women did not correlate with the mean HAM-A score. Conclusion Unexplained primary and secondary infertile couples had similar anxiety scores before the commencement of fertility treatments. However, the scores were higher in women than their male partners. Since the burden of treatment and the likelihood of treatment failure might increase the level of anxiety the women could be offered proper cognitive coping and relaxation interventions.
Keywords: Infertility; anxiety; unexplained infertility; ASSISTED REPRODUCTIVE TREATMENT; QUALITY-OF-LIFE; PSYCHIATRIC-DISORDERS; UNITED-STATES; WOMEN; DEPRESSION; PREVALENCE; DISTRESS; STRESS; MEN